KADAR SIANIDA DALAM SAYURAN DAN UMBI-UMBIAN DI DAERAH GANGGUAN AKIBAT KURANG YODIUM (GAKY) - Ance Mudiana; Sukati Saidin (Persagi, 2001)
Cyanida Contents of Vegetables and Tubers In Areas of Iodine Deficiency Disorders.Background: Thiocyanate goitrogenic shows different ways to prevent iodium absorption by thyroid gland. Thiocyanate is a result of detocification from cyanide content in food which occurs in the body then is excreted through urine. Cyanide is generally found in cabbage, cassava, bamboo shoot, chinese cabbage and